Financial Strategy of Cultured Accessories Through Resin (Aberasi) - Afda Widyanti Nasution; Muhammad Yamin; Ihsan Effendi (Universitas Medan Area, 2022)
Handicrafts in Indonesia still have many shortcomings, one of which is not durable, that's why the researchers made ABERASI, resin-based accessories that are more durable and can make accessories look more beautiful. This study aims to see whether ABERASI is a viable business to run by considering sales, Return On Assets (ROA), Return On Investment (ROI), and Payback Period (PP). The research methods used are qualitative methods and sampling techniques. (informants) namely snowbal sampling and data collection techniques using questionnaires, interviews. And documentation. The results show that ABERASI sales are 152 units per month, ROA is 58% greater than the industry standard, which is 5.98% which means it is feasible to run, ROI is 153% greater than the industry standard is 30% which means it is feasible to run, and PP is 6 month is greater than 1 year (economic age) which also means it is feasible. So it can be concluded that the ABERASI business is feasible to run.